Analisis Keberlanjutan Perkebunan Kelapa Sawit Rakyat di Kecamatan Parindu Kabupaten Sanggau - Robertus Imanuel; Maswadi; Wanti Fitrianti (Jurnal Riset Rumpun Ilmu Tanaman, 2026)
Oil palm plantations are often confronted with the problem of uncontrolled land expansion and suboptimal management, which potentially threaten the sustainability of the business from environmental, social, and economic perspectives for surrounding communities. This condition calls for a comprehensive evaluation of management practices implemented by independent smallholders. This study aims to determine the sustainability status of smallholder oil palm plantations in Parindu Subdistrict, Sanggau Regency, assessed from five main dimensions: ecological, economic, social, institutional, and technological. In addition, the study analyzes attributes that have sensitivity levels affecting the future sustainability of oil palm farming as a basis for formulating improvement strategies. A total of 36 respondents were selected using purposive sampling techniques and in-depth interviews. The research method employed was quantitative descriptive using the Rap-Palmoil approach and qualitative descriptive supported by kite diagrams to clarify the analysis results. The findings indicate that the management status of oil palm plantations falls into the moderately sustainable category, with MDS values of 53.61 for Embala Village and 55.75 for Maju Karya Village. The dimensions that require priority improvement in both villages are the ecological and technological dimensions.